An Evaluation of Malaria Control Practices by Caregivers of Under-5 Children in Calabar South Local Government Area of Cross River State, Nigeria - Andrew, Agbenin; Akpan, Edem A. (International Journal of Innovative Research in Medical Science, 2019)
Background: Despite many years of research and concerted efforts at control of malaria, the achievement of a malaria free world remains a dream. The prevalence of the disease continues to increase in many parts of the world especially among under-5 children and pregnant women. However, in Nigeria, the scale up of malaria control strategies has produced recognizable public health impact in several communities and this has led to the development of new tools and strategies, including integrated approach to control, aimed at further consolidating malaria control goals. Objectives: To evaluate malaria control practices by Caregivers of under-five children in Calabar South LGA, Cross River State, Nigeria. Methods: A cross sectional study involving the administration of questionnaires to 440 Caregivers of under-five children selected through a multi-stage sampling and simple random sampling techniques. The administration of the questionnaires to the respondents was used to evaluate malaria control practices by Caregivers of under-5 children in Calabar South LGA since the launch of the Roll back Malaria (RBM) Program in Nigeria in 1998. Results: The sociodemographic characteristics of respondents are as follows: 35.3% of respondents fell within the age brackets of 26-31 years, 85% were married, 56.3% had, at least, secondary school education, 35.8% were traders, 98.5% were Christians, 40.8% were medium income earners, 56.3% had 3-5 persons per household. Evaluation of Caregivers in the LGA on knowledge of malaria control practices, show they had good knowledge on strategies to control malaria but many of them did not practice them in their homes. The very few that were involved in the practice of malaria control activities rely on vertical approaches to control instead of integrated malaria control efforts as advocated during the launch of the RBM program in Nigeria in 1998. Conclusions: The state Ministry of Health, Calabar, Cross River State, Nigeria, through the Department of Public Health, needs to invest more on education, communication and information dissemination strategies to reach Caregivers of under-5 children to adopt integrated approach to malaria control instead of using isolated vertical approach if they are to achieve the malaria control targets set by RBM and MDGs for under-5 children in Nigeria in general and Calabar South LGA in particular.